Farm to policy: Socioeconomic dynamics and occupational challenges of freshwater fish farmers in the Cauvery Delta region, Tamil Nadu - S. Dawood Ibrahim; V. Senthilkumar; T. Umamaheswari; R. Durairaja (Journal of Fisheries, 2026)
Freshwater aquaculture is vital for global food security and rural livelihoods. This study examined 120 fish farmers across Thanjavur, Thiruvarur, and Nagapattinam districts in Tamil Nadu's Cauvery Delta to understand socioeconomic dynamics and constraint hierarchies shaping aquaculture development. Using structured interviews and Garrett ranking, the research revealed critical structural vulnerabilities: the farming population is predominantly male (93.3%), aging (average 45 years; 79.2% middle-aged or older), and faces future labour succession challenges despite relatively high literacy (85% educated). Low organizational participation (54.2% non-members) undermines collective bargaining capacity. Most farmers (80.8%) combine aquaculture with other occupations, reflecting income insufficiency rather than strategic diversification. With 65% representing first-generation farmers averaging eleven years' experience, aquaculture emerges as recent livelihood diversification rather than traditional practice. Landholding patterns showed 75% farm ownership averaging 3.5 acres, though 53.3% operate small farms below three acres, limiting economies of scale. Caste composition revealed predominance of marginalized communities—61.7% Other Backward Class and 27.5% Scheduled Caste—facing systematic barriers to credit, technology, and market access. Constraint analysis identified high feed costs as the primary short-term barrier across all districts, followed by insufficient credit access and inadequate extension services, while low farm gate prices emerged as the dominant long-term constraint. Findings demonstrate that effective aquaculture policies must address structural inequities rooted in caste-based exclusion, land fragmentation, organizational deficits, and market asymmetries through targeted interventions including collateral-free credit, farmer producer organizations, district-level feed cooperatives, and differentiated extension programming to transform aquaculture into dignified, profitable livelihoods.